PENGARUH KEPUTUSAN INVESTASI DAN KEPUTUSAN PENDANAAN PADA NILAI PERUSAHAAN - Ni Kadek Ari Mayningsih; Putu Nuniek Hutnaleontina (UNHI Press, 2021)
The value of the companyll is the investor's perception of the success rate of the companies which are related to the share price. The objectives of this research are to find out the effect of investment decisions, investment decisions, and funding decisions, etc. on company values ​​etc. in the manufacturing of the Food and Beverages sub-sector, which are listed in the Indonesian Stock Exchange III 2014-2018. The population in this research is all food and beverage sub-sector companies which are listed in the Indonesian Stock Exchange in 2014-2018 as many as 26 companies, the method of determining samples in this research is all by using the purposive sampling method. A total of 11 samples obtained were 11 companies. Types of data used in this research are all secondary datall, data analysis techniques etc. used in this research are all descriptive statistical analysis, classical assumption test, multiple regression analysis, F test and etc. Darill's research results can be seen that: 1) The investment decision II measured by the Pricell Earnings 11 Ratioll (PER) has a positive effect on the firm's value) seen from the value of the significance level of 0.000 (sig. <0.05) with a coefficient of 0.170 2) Funding decisions III are measured by Debt toll Equity Ratioll (DER) and have a significant negative effect on the company's variable values ​​etc. seen from the significant values ​​of 0.027 and the coefficients of funding decisionsll is -1.207 This means variable debt equity decisions etc are measured by Debt toll Equity Ratioll etc. ) has a significant negative effect on the variable value of the company. So it can be said that all H2 is rejected or not supported. This will explain that the decision and funding that a company will do is to use all funding through debt etc. which is more than using all funding through equity.